Analisis Organoleptik (Scoring Test) Tingkat Kesegaran Ikan Nila Selama Penyimpanan - Ayu Kalista; Amin Redjo; Umi Rosidah (Jurnal FishtecH, 2018)
Sensory analysis has been used to to detect changes in the degree of tilapia freshness during the 12 hour storage period. This research was conducted in March 2017 until aJuly 2017. This research was conducted at Food Laboratory of PDD Polinela of Banyuasin Regency. The research method used is the experimental method (Explanatory Research). The data were processed using Friedman Conover and analyzed descriptively. The quality of fish can be grouped into several categories namely high quality, good quality, limit of acceptability and spoilt. The results showed the longer the time of retreat the quality of fish Tilapia was alight. High quality category has a gill color score of 8.40, texture 7.64 and aroma 7.76. Good quality category has a gill color score of 6.44, texture of 6.76 and aroma of 5.24. The limit of acceptability category has a gill color score of 4.72, a texture of 4.56 and a scent of 5.24. The spoiled category has a gill color score of 4.72, 3.16 texture and 2.44 odor.